Balinese Addressing Terms and their English Translation in Balinese Folklore - Susanthi, I Gusti Ayu Agung Dian; Kardana, I Nyoman; Budiarta, I Wayan; Warmadewi, Anak Agung Istri Manik (International Journal of Psychosocial Rehabilitation, 2020)
Bali has a very unique tradition and culture, one of them is its language. Balinese language has its own structure and the degree of politeness in using it. It depends on who speaks it to whom and the certain situation or condition it is being spoken. According to Sor Singgih Basa, Balinese itself is divided into the four levels, namely: Basa Alus Singgih, Basa Alus Madya, Basa Kasar. These politeness level are related to the traditional level of society. This present research deals with meaning of Balinese addressing term. The Balinese addressing terms discussed in this research cover the addressing term which represents the traditional life of Balinese society. The meaning components analysis which related to semantics theory is applied in this present research, this meaning components analysis will help to understand about the meaning of the Balinese addressing terms. The theories adopted in this present research are meaning components by Larson (1998), the basic principles in translation by Nida (1975) and the translation procedures by Vinay and Darbelnet (in Venuti, 2000). There are some addressing terms which presented in this study: the addressing terms used by the characters on fable, the addressing terms used by the traditional society which depends on the level of the society in Bali.